Unlocking Economic Dynamics: A Comprehensive Study of Major Sporting Events and Their Impact on Host Cities - Chavda, Kishan; Chuahan, Rahul (Indonesian Journal Publisher, 2024)
This research investigates the economic impact of major sporting events on host cities, analysing both the advantages and challenges associated with hosting such events. Through a comprehensive literature review and methodological approach combining quantitative and qualitative analysis, the study examines age and gender dynamics in perceptions of economic benefits derived from these events. Findings reveal that age and gender influence attitudes towards the economic impact of major sporting events, with a significant interaction effect observed. While age and gender differences contribute to variations in support for hosting such events, the effect sizes remain modest. The study underscores the importance of tailored approaches that account for demographic nuances in event planning and policy formulation.